'The Workers and the War: a Programme for Labour' was written by Sidney Webb and distributed by the War Emergency Workers' National Committee (WEWNC) in 1914 (1914)
1914 1914-1918 "'The Workers and the War: a Programme for Labour' was written by Sidney Webb and distributed by the War Emergency Workers' National Committee (WEWNC) in 1914" [T0252.jpg], 1914 The Committee was established on 5 August, 1914 at the conference called by the Joint Board [comprising the Trades Union Congress, General Federation of Trade Unions and the Labour Party].